2014
DOI: 10.1051/e3sconf/20140301009
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Green Construction in Malaysia: Industrialised Building System (IBS) vs Traditional Construction Method

Abstract: Abstract. This study is conducted to compare between the two approaches of construction. It is carried out through case studies on construction sites, distribution of a total of 100 questionnaires as well as interviewing respondents who are related to this discourse. The case studies for this research were carried out at four construction sites within the Malaysian state of Penang. Two case studies used Industrialised Building System method while the remaining two deployed the traditional method of constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…In 2005, the author defined industrialization as "catering a large market, by investing in technologies that simplify production and also reduce cost" [10]. Other authors refine the definition by saying manufacture takes place in a specialized and controlled facility [11][12][13][14]; site work is minimized [12,13,15]; mechanical equipment is used [12,14,15]; and a systematic approach is involved [12].…”
Section: Industrialized Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2005, the author defined industrialization as "catering a large market, by investing in technologies that simplify production and also reduce cost" [10]. Other authors refine the definition by saying manufacture takes place in a specialized and controlled facility [11][12][13][14]; site work is minimized [12,13,15]; mechanical equipment is used [12,14,15]; and a systematic approach is involved [12].…”
Section: Industrialized Constructionmentioning
confidence: 99%
“…Most frequently, the potential of increased productivity, production speed, and the control on quality and lead-times is mentioned [10,11,13,14,16]. In a European society that is characterized by a lack of skilled-labor and a pressing need for new construction on urbanized and spatially limited locations, industrialized construction can offer a solution that is less dependent on labor and offer construction workers a healthier and safer working environment [11][12][13][14]16]. Although significant capital investments to facilitate an industrial factory environment are made with a long-term perspective [14], reduced production cost can be a direct result that leads to more affordable buildings [12,13,16].…”
Section: Industrialized Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional on-site construction methods have been popular since the end of the 19 th century (Mydin et al, 2014;Kamali et al, 2016). These methods are also defined as "sitebuilt" or "conventional" construction and refer to construction being built on site after the design is done and the contractor is awarded the contract.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys such as that conducted by [2] have shown that, a variety of building construction techniques have been created to provide convenience to consumers. Creation of new construction techniques affects the construction processes amongst them expedite construction processes, save time and cost.…”
Section: Introductionmentioning
confidence: 99%